2012
DOI: 10.1007/s10384-011-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective-wavelength block filters on pupillary light reflex under red and blue light stimuli

Abstract: These results suggest that the mRGC in humans may respond to 470-nm-wavelength light at 100 cd/m(2), and there is a possibility of affecting the sustained phase of the light reflex without changing visual performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…For example, selectively blocking exposure to short-wavelength light (e.g., using specialized goggles) has been shown to prevent the suppressive effects of moderately-bright white light on melatonin production26272829. Analogous findings have been reported for the pupillary light reflex, in which filtering of short-wavelength light (460 nm to 480 nm) reduced sustained pupillary constriction responses to a bright blue light stimulus (470 nm, 100 cd m −2 )30. In contrast to studies that have examined the immediate effects of a blue-blocking intervention (i.e., over minutes or hours), a recent study showed that blocking short-wavelength light ( < 550 nm) continuously for 2 weeks altered the sensitivity of melatonin suppression31.…”
Section: Discussionmentioning
confidence: 62%
“…For example, selectively blocking exposure to short-wavelength light (e.g., using specialized goggles) has been shown to prevent the suppressive effects of moderately-bright white light on melatonin production26272829. Analogous findings have been reported for the pupillary light reflex, in which filtering of short-wavelength light (460 nm to 480 nm) reduced sustained pupillary constriction responses to a bright blue light stimulus (470 nm, 100 cd m −2 )30. In contrast to studies that have examined the immediate effects of a blue-blocking intervention (i.e., over minutes or hours), a recent study showed that blocking short-wavelength light ( < 550 nm) continuously for 2 weeks altered the sensitivity of melatonin suppression31.…”
Section: Discussionmentioning
confidence: 62%
“…However, after the discovery of ipRGCs, pupillometric studies have shown the importance of including color stimulation (Hattar et al, 2002). It seems that at 100 cd/m 2 , these cells have peak sensitivity to 470 nm wavelength (Ishikawa et al, 2012) and they participate in the pupil light reflex response (Provencio et al, 2000; Berson, 2003; Hatori and Panda, 2010; Schmidt et al, 2011). Blue light is often used to measure ipRGC function (Herbst et al, 2012), whereas red light is used to asses outer retina functioning (rods and predominantly cones) (Leon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The 470 nm blue light used in this study stimulates not only the photoreceptor cells, but also mRGCs. [5][6][7][8] In the report of Tarttelin et al concerning the time of expression of opsin during early stages of development, melanopsin was present, but rhodopsin was not observed in human embryos at 8-13 weeks gestational age. 10 Our present findings are consistent with those of Hanita et al and Tarttelin et al 9,10 Generally, vision can be classified into two types: image forming and non-image forming.…”
Section: Discussionmentioning
confidence: 99%